Early-maturing varieties of open-ground tomato of domestic breeding in the conditions of the Tersko-Sulak subprovincion of Dagestan - P. M. Akhmedova (Овощи России, 2023)
Relevance. Dagestan is a zone of prosperous agriculture, distinguished by the abundance of heat, sun and irrigation in the plain zone. Tomatoes occupy a special place among vegetable crops in the world, including in the Republic of Dagestan. Determinant varieties are now the most common in the production of tomatoes, especially in the open ground. The main areas of specialized cultivation of tomatoes in the open ground are concentrated in the Kizlyar and Derbent districts of plain Dagestan. In these areas, there are high average daily temperatures for the formation and ripening of tomato fruits in excess, which is favorably reflected in the overall productivity of the bushes. Whereas in the foothills of Dagestan, insufficient heat resources do not allow growing tomato varieties with a long growing season. In the foothill part of the republic there is a large labor-resource potential, vegetable growing, as a labor-intensive type of agribusiness, acts as a sphere of employment for a significant part of the rural population. The demand for tomato varieties with a short growing season in this part of the republic is great.Methods. The research was carried out on the basis of the Tersko Sulak subprovincion of the FGBNU of the FANC RD of the Kizlyar district. The soil of the experimental site is alluvial-meadow, medium-saline, medium loamy in mechanical composition. Agrotechnics is generally accepted in the Republic of Dagestan for tomato culture.Results. The method for the study was the new semi-stamp cultivars of FGBNU FNCO (VNIISSOK) selection: Fakel (counter), Blagodatny, Viking, Voskhod VNIISSOKa, Magnat, Severyanka, Sodruzhestvo, Perst, Patrice. According to the maturation dates, the samples were divided into three groups: very early – Severyanka, Blagodatny, Magnat, Voskhod VNIISSOK (97-100 days); early – Patrice, Viking, Perst (102-105 days); middle-early – Sodruzhestvo, Fakel (111-114 days). According to the type of bush, we have identified 5 ordinary and semi-lamb samples with a height of no more than 78 cm. Two samples had a height of 50-53 cm (Patrice, Perst) and an average fetal weight of 72 and 60 g. Three samples had a height of 70, 71, 72 cm (Voskhod VNIISSOKa, Blagodatny, Sodruzhestvo) and an average fetal weight of 107, 110, 130 g. According to the output of gross output, the best indicators were of the following varieties: Blagodatny – 86.3; Voskhod VNIISSOKa – 82.7; Sodruzhestvo – 77.6 t/ha; Patrice – 68.2 t/ha. The following grades had  a high yield of marketable products: Voskhod VNIISSOKa, Patrice – 92%; Blagodatny – 91%; Perst – 90%. The varieties also have a relatively high dry matter index of 5.3-6.4%.